Efficacy of a simple intravitreal perfluoropropane injection in treating unclosed idiopathic macular holes following vitrectomy - Zexia Dou; Jindong Han; Shaozhen Zhao (BMC Ophthalmology)
Abstract Background This study aimed to evaluate the efficacy of a simple intravitreal injection of perfluoropropane (C3F8) in treating unclosed idiopathic macular holes (IMHs) in patients who had previously undergone primary pars plana vitrectomy (PPV). Methods This study was a retrospective, observational clinical study. It included patients diagnosed with unclosed IMHs following primary PPV combined with internal limiting membrane peeling and air tamponade. Optical coherence tomography (OCT) performed 1 week after PPV revealed unclosed IMHs with the presence of the ‘cuff’ sign and intraretinal cysts. The following day, these patients received a simple intravitreal C3F8 injection. Comprehensive evaluations, including best-corrected visual acuity (BCVA), indirect ophthalmoscopy, fundus photography, and OCT, were performed before PPV, 1 week after surgery, and at follow-up intervals of 1–3 months after the intravitreal gas injection. Results The minimum linear diameter (MLD) of the macular holes (MHs) 1 week before C3F8 injection was 335.1 ± 74.3 μm. Following C3F8 tamponade, the closure rate of the MHs was 100%. The mean BCVA before C3F8 tamponade was 0.68 ± 0.17 logMAR (20/100) after primary PPV, which improved to 0.48 ± 0.19 logMAR (20/63) after C3F8 tamponade, showing a statistically significant difference (P = 0.01). Conclusions For patients with unclosed MHs after primary PPV, the presence of the ‘cuff’ sign on OCT suggests that retreatment can be effectively achieved through a simple intravitreal gas injection. This approach is straightforward, practical, and effective.